Empirical impact of China-Pak business cycle synchronization on environmental degradation in Pakistan - Huang, Yongming; Xu, Fan; Abbas, Ali; Cong, Phan The; Zhang, Yuanwei; Kim, Euijune (Frontiers in Environmental Science, 2023)
This study investigates the empirical impact of China-Pak business cycle synchronization, urbanization, foreign direct investment, exports, imports, and financial development on environmental degradation in Pakistan from 1975 to 2017. In doing so, we used the Hodrick-Prescott filter to obtain the trend component of GDP. Then the trend component was subtracted from the original series of GDP to capture the cyclical component of China and Pakistan. Synchronization between business cycles of both countries was estimated using the business cycle synchronization index. Phillips Perron and Augmented Dickey-Fuller unit roots tests were employed to check the stationarity of all variables. The results showed that all variables were stationary with a mix of level and first difference. The existence of cointegration was confirmed through the F-Bounds test. Except for FDI, all other explanatory variables were found to be significant factors of environmental degradation in the model. Long-run estimates were through the ARDL method, and results showed that imports, financial development, and urbanization positively and significantly impacted environmental degradation in Pakistan. At the same time, China-Pak business cycle synchronization and exports were found with negative and significant coefficients for environmental degradation in Pakistan. ECM value was negative and significant, which showed convergence in the model and a short-run relationship in the model. This study also used the VAR Granger Causality test developed by Toda-Yamamoto (1995) to check the causality linkage among the variables. The study suggested by relying on empirical findings that improvement in China-Pak business cycle synchronization can be an environment-friendly factor in Pakistan. An increase in exports and a decrease in imports can play an essential role in reducing environmental degradation in Pakistan. A favorable balance of payment can provide sufficient financial prosperity to take environmental preservation measures. Financial development provided to the private sector should be observed critically to ensure that production units are not causing much carbon emissions. Narrowing urbanization can also be a significant measure to uplift Pakistan's quality of the environment.